Cell-free DNA in medium is associated with the maturation ability of in vitro cultured oocytes - Yasuhisa MUNAKATA; Koumei SHIRASUNA; Takehito KUWAYAMA; Hisataka IWATA (The Society for Reproduction and Development, 2019)
Follicular fluid contains cell-free DNA (cfDNA), which may serve as a useful biomarker of oocyte ability. The present study evaluates whether nuclear and mitochondrial cfDNAs in conditioned oocyte growth medium determine the quality of oocytes cultured in vitro. Oocyte and granulosa cell complexes (OGCs) derived from early antral follicles of gilt ovaries were cultured for 14 days and the amount of cfDNA and lactate concentration in the conditioned culture medium were measured and compared to evaluate oocyte maturation ability. The amount of nuclear cfDNA, but not mitochondrial cfDNA, strongly correlated with the number of dead cells in OGCs. Furthermore, low mitochondrial cfDNA content and high lactate concentration in the medium was associated with high maturation ability of oocytes cultured in vitro. In conclusion, the amounts of nuclear and mitochondrial cfDNAs differentially reflect the conditions of OGCs, and low mitochondrial cfDNA, low glucose content, and high lactate concentration in the medium are associated with the proper maturation of oocytes.